Pengelolaan Likuiditas Bank Syariah - Ichsan, Nurul (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2014)
Islamic Banking Liquidity Management. This article is about management of liquidity which discuss about the position of cash money in the company and its ability to fulfill the obligation (pay the debt) on time. Management of liquidity is one of the essential function which is done by banking institution and inside its efficient management, is needed instrument and finance market which is taking not only short term but also long term, and not only conventional banking but also syariat. Through that natural necessity (placement and fulfillment of short term need), for Islamic banking in Indonesia has been availabled some instruments such as (IMA) certificate of Mudhorobah Investment between bank, (PUAS) market banking regulations between syariat bank, (SWBI) Bank of Indonesia Wadiah certificate, (FPJPS) provision about short term cost facility for Islamic banks  DOI:10.15408/aiq.v6i1.1371